Principles for the Effective Development of Ideological and Political Education Theory Courses in Universities in the New Era - Wu, Yanle (Journal of Theory and Practice of Contemporary Education, 2023)
The research on the effective development of ideological and political education in universities in the new era aims to implement and improve the effectiveness of current ideological and political theory education in universities, thereby achieving the goal of comprehensive education. To achieve this goal and implement this requirement, ideological and political education workers in universities need to promptly identify their existing problems and seek targeted solutions.